Vozes de formadoras: limites e possibilidades na formação do professor pesquisador/reflexivo - Simone Grace de Paula (2003)
The present work main objective was to understand and analyse the social representations about the researcher-teacher, that were constructed by university teachers, during the conclusion of the Graduate Course of Teachers Training for initial years of Elementary School from 1997 to 1999, in the Faculdade de Educação da Universidade do Estado de Minas Gerais. The specific aims of the work were: to identify the established relations among the other training axes (the linking theory/practice and the integration among school subjects); to recover the reflections of the university teachers about the experiences and social practices in the construction of the perspective of the researcher teacher training; to map the challenges and the difficulties that were found in the structuring and Proposal. The qualitative research was developed through the study of case. The instruments used in data collection were the questionnaire, the interview and the documents analysis elaborated by the research subject. The data were studied in qualitative and quantitative ways, having as reference the consulted bibliography. The theoretical basis to the main questions of this work was investigated on Kenneth Zeichner work and other authors that take part in an international movement that supports the training of a reflective teacher: some authors who study social representation as a phenomenon and not as a methodology, were investigated too. It was necessary to recover the pedagogical practices that were constructed with the objetive of educating the researcher/reflective teacher through maping the faced challenges and learning about the social representation that guides these practices. The results showed that there are heterogeneous social representations about the researcher/reflective teacher that, on the one hand, make the formative process to enrich and, on the other hand, caused tension on the development of practical activities. The analyses of the formation process guided to changes on the professional profile that the teachers intend to form, that is, from the researcher teacher to the reflective practioner.